Data science essentials - Pierson, Lillian (John Wiley & Sons, Inc., 2025)
Data Science Essentials For Dummies is a quick reference on the core concepts of the exploding and in-demand data science field, which involves data collection and working on dataset cleaning, processing, and visualization. This direct and accessible resource helps you brush up on key topics and is right to the point-eliminating review material, wordy explanations, and fluff-so you get what you need, fast. Perfect for supplementing classroom learning, reviewing for a certification, or staying knowledgeable on the job, Data Science Essentials For Dummies is a reliable reference that's great to keep on hand as an everyday desk reference.
Includes index
Keywords: Information technology; Information retrieval; Databases; Data mining; Technologie de l'information; Recherche de l'information; Exploration de données (Informatique); information technology; information retrieval